HUMAN SYNGAMOSIS - 2 CASES OF CHRONIC COUGH CAUSED BY MAMMOMONOGAMUS-LARYNGEUS - Delara, TDC; Barbosa, M. A.; Deoliveira, M. R.; DEGODOY, I; Queluz, Thais Helena Abrahão Thomaz [UNESP] (Amer Coll Chest Physicians, 1993)
Parasites of the genus Mammomonogamus may occasionally affect the human respiratory tract, causing human syngamosis. We describe two cases of chronic unproductive cough caused by Mammomonogamus laryngeus that occurred in the state of São Paulo, Brazil. Some aspects related to human parasitism, diagnostic approach, and treatment are discussed.